Work in Progress: Transforming laboratory learning experiences for Industrial Engineering education during the COVID-19 pandemic - Garay-Rondero, Claudia Lizette; Salinas-Navarro, David Ernesto (IEEE, 2022)
The COVID-19 pandemic has set instructional barriers to engineering courses because of the limited access to learning resources and infrastructure. However, there is still the need for active alternatives for high-impact learning. This work explores the transformation of laboratory courses for Industrial Engineering education using Experiential Learning under remote learning spaces. The authors explore the current alternative efforts and propose a framework to face disruptive circumstances. These ideas were further implemented in two application cases over the last year. This work contributes to the enrichment of engineering learning experiences by considering novel learning situations and contextual conditions in labwork. ©The authors, IEEE.